Preoperative decompression for left-sided obstructive colorectal cancer: a comparative study between a stent and a decompression tube - Xin-Chun Guo; Qiang Lu; Yu-Fei Fu; Xin Lu (Videosurgery and Other Miniinvasive Techniques, 2025)
Introduction: Stents and decompression tubes (DTs) are both commonly utilized for preoperative decompression in patients with left-sided obstructive colorectal cancer (OCRC). However, the comparative effectiveness and oncological safety of these 2 approaches remain uncertain.